ENHANCING VOCABULARY SKILLS FOR YOUNG LEARNERS USING CROSSWORD PUZZLE MOBILE GAME - Gede Hermawan Adi Prayoga (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Vocabulary is a very important skill in learning English. Therefore, effective vocabulary learning is needed to support the development of English. Mobile games are one of the media that can be implemented in vocabulary learning. Mobile games are used because they are fun and can attract students' attention in learning. The use of crossword puzzle games in vocabulary learning is the focus of this study. The crossword game used is based on a mobile game, namely "Words of Wonders: Crossword to Connect Vocabulary". The data is taken from various sources using library research methods. The paper found that the majority students who are taught by using Crossword Puzzle game is more engaging in learning and showing the increase in their score. Furthermore, the use of Crossword Puzzle game is a proper way in teaching vocabulary and can be used as a supplementary material in order to make students are more engage in the learning.